Does lung cancer screening with low-dose computerized tomography improve survival?. (23rd July 2021) - Manuel, Lucy; Fong, Laura S; Ly, Thompson; Meredith, Graham
Summary: A best evidence topic in thoracic surgery was written according to a structured protocol. The question addressed was 'Does lung cancer screening with low-dose computerised tomography (LDCT) improve survival?' More than 963 papers were found, of which 8 randomized control trials and 1 meta-analysis represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers were tabulated. The majority of studies trended towards greater incidence of early lung cancer detection, and subsequent curative treatment, in the LDCT screening populations with appropriately powered randomized control trials (NELSON and NLST) demonstrating survival benefits of >20% in lung cancer-specific mortality. However, this reduction must be evaluated against the potential harms associated with screening, including complications from diagnostic procedures, and costs of overdiagnosis, as evidenced in several studies. We conclude that in high-risk populations, lung cancer screening with LDCT results in earlier detection of low-stage cancers and improved survival when compared to usual clinical care or screening with a chest X-ray. Abstract : A best evidence topic was constructed according to a structured protocol.